Gestão da qualidade: um estudo base na avaliação dos pacientes de um hospital universitário em Belém do Pará - ANDRADE, Rosa Cristina Autran (Universidade Federal do Pará, 2019)
The evaluation of the quality perceived by the client is configured as a strategic tool for the management of services, including health services, used to identify the perception of customers (patients and caregivers) in relation to services provided by hospitals, by lifting data to enable the identification of gaps in certain areas and to correct the problems. Understanding this construct can contribute to significant improvements to the hospital, its customers and workforce. In this context, the objective of this research was to evaluate the quality of services provided by the customers' perception regarding the assistance of university study hospital. Thus, we seek to obtain information allowing to identify strengths and weaknesses of specific areas in which improvements need to be implemented or enjoyed advantages in order to increase customer satisfaction met in the sector and the provision of quality services to these clients and consequently the future vision scope and objectives of the organization. The methodology adopted for this research was the quantitative approach of descriptive and exploratory. We carried out a cross-section survey ex post facto through field research during the months from October to December of 2014. Data collection was conducted through structured questionnaires. The data used was the quantitative, using techniques of descriptive and multivariate statistics